EVALUATION OF WOUND HEALING AND ANTIBACTERIAL PROPERTIES OF METHANOLIC ROOT EXTRACT OF STEPHANIA DINKLAGEI (ENGL.) DIELS - Udegbunam, Sunday Ositadimma; Igbokwe, Nnabuike Prince; Udegbunam, Rita Ijeoma; Anyanwu, Madubuike Umunna; Nnaji, Thoephilus Okafor (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Stephania dinklagei Diels (Engl.) is used in folkloric medicine in Southeastern Nigeria for treatment of wounds and some bacterial-associated infections. This study evaluated the wound healing and antibacterial potential of Stephania dinklagei to validate or invalidate its folkloric use.Methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of methanolic extract of S. dinklagei root (MESDR) against Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Klebsiella spp. was determined by macrobroth dilution. The extract at 20% and 10% concentrations were dosed orally to rats at 300mg/kg body weight (bw) in incision and dead space wound healing model to determine wound tensile strength and granulation tissue weight, respectively. Same extract concentrations were applied topically in excision wound model to determine the rate of wound contraction and epithelialization. Activities of superoxide dismutase (SOD), catalase (CAT), and the levels of total protein (TP), malondialdehyde (MAL), hydroxyproline (HYP) and hexosamine (HEX) in excision wound biopsies were determined at days 7 and 14 post wounding (pw). In the excision wound model, the extract concentrations were compared with gentamicin sulphate.Results: The MIC of S. dinklagei extract against P. aeruginosa, S. aureus, B. subtilis, E. coli and Klebsiella spp. were 8mg/ml, 3 mg/ml, 5mg/ml, 6mg/ml and 7mg/ml, respectively, while the corresponding MBC were 10 mg/ml, 5 mg/ml, 7mg/ml, 8mg/ml, and 9 mg/ml, respectively. The 20% extract concentration gave significantly (P<0.05) higher tensile strength and granulation tissue weight than the 10% concentration and gentamicin sulphate. Wound contraction and epithelialization occurred significantly (P<0.05) better and faster in wounds of animals treated with the 20% extract concentration and gentamicin sulphate compared to those treated with 10% extract concentration. TP of animals treated with 20% extract concentration and those treated with the reference drug did not vary significantly (P>0.05) at day 14 pw. SOD and CAT activities, and MDA and HEX level of all the groups did not vary significantly (P>0.05) at day 14 pw. HYP level of the extract-treated groups significantly (P<0.05) decreased against the control. No significant difference existed in HYP level between the extract-treated groups. Conclusions: S. dinklagei possess antibacterial property and wound healing property which is comparable to that of gentamicin sulphate.